High-intensity interval training for patients with coronary artery disease: Finding the optimal balance. (1st January 2020) - Keech, Andrew; Holgate, Katie; Fildes, Jennifer; Indraratna, Praveen; Cummins, Leigh; Lewis, Chaminda; Yu, Jennifer
Abstract: Background: The optimal characteristics of high-intensity interval training (HIIT) for patients with coronary artery disease (CAD) within cardiac rehabilitation (CR) are unclear. We assessed a HIIT protocol designed to balance patient safety, efficacy and enjoyment. Methods: Twenty-nine patients with CAD completed 6-weeks (× 2 sessions per week) of HIIT within outpatient (phase 2) CR. HIIT comprised 15 repetitions × 30-seconds cycling at ∼85-90% maximum heart rate, interspersed with 30-seconds of active recovery. Key outcomes covered patient safety, efficacy (peak aerobic capacity, body composition, blood pressure and vascular function), and patient adherence and enjoyment. Results: No cardiovascular-related adverse events were reported in relation to HIIT sessions. Patients showed significant improvement in peak aerobic capacity (mean +12%, p < 0.001, effect size d  = 0.38), blood pressure (brachial systolic -7mmHg, p < 0.001, d  = -0.59) and total body fat (-4%, p < 0.001, d  = -0.49). Central adaptations were prominent (aortic systolic BP -5mmHg, p  = 0.001, d  = -0.50; visceral fat -10%, p  = 0.001, d  = -0.41). Patient enjoyment of training was high (5.5 out of 7 using the Exercise Enjoyment Scale) and measures of affective state improved following training (assorted p < 0.018). Conclusions: This HIIT protocol appears safe, effective and enjoyable for patients with CAD within CR. Improved aerobic fitness, blood pressure and body fat levels were observed indicating improved cardiovascular-risk. High patient enjoyment and improved mood suggest the HIIT could be sustainable for patients in the longer-term. Highlights: This HIIT protocol designed specifically for patients with CAD appears safe, effective and enjoyable. Positive changes in aerobic fitness, body composition and blood pressure, indicating lowered CV risk.